(untitled) - Pollard, Andrew (London, 2008)
Author provides a professional development text for new and experienced teachers on becoming a more reflective teacher, with discussion of specific elements of the teaching-learning process that include reflective classroom activities and discussion of classroom topics such as organization and assessment. This edition offers information on assessment, learning how to learn, and pupil consultation, and Personalized Learning and Every Child Matters policies in the UK. In addition to other updates, it has been revised to reflect teaching standards and competencies in the UK and includes research briefings from the Teaching and Learning Research Programme. (booknews.com)
Keywords: Elementary school teaching,Teachers,Dạy học ở tiểu học,Giáo viên; Self-rating of,Tự xếp loại